Isolation and genomic structure of a human homolog of the yeast periodic tryptophan protein 2 (PWP2) gene mapping to 21q22.3. - Lafrenière, R G; Rochefort, D L; Chrétien, N; Neville, C E; Korneluk, R G; Zuo, L; Wei, Y; Lichter, J; Rouleau, G A (Genome Research, 1996)
As part of efforts to identify candidate genes for disease mapping to the 21q22.3 region, we have assembled a 770-kb cosmid and BAC contig containing eight tightly linked markers. These cosmids and BACs were restriction mapped using eight rare cutting enzymes, with the goal of identifying CpG-rich islands. One such island was identified by the clustering of NotI, EagI, SstII, and BssHII sites, and corresponded to the NotI linking clone LJ104 described previously. A 7.6-kb HindIII fragment containing this CpG-rich island was subcloned and partially sequenced. A homology search using the sequence obtained from either side of the NotI site identified an expressed sequence tag with homology to the yeast periodic tryptophan protein 2 (PWP2). Several cDNAs corresponding to the human PWP2 gene were identified and partially sequenced. Northern blot analysis revealed a 3.3-kb transcript that was well expressed in all tissues tested. A cDNA consensus of 3157 bp was obtained, and an open reading frame potentially encoding 919 amino acid residues was identified. The predicted protein shows 42% identity and 57% similarity at the amino acid level to the yeast PWP2 protein, which is a member of the WD-repeat containing superfamily, and potentially encodes a G-protein beta subunit. The PWP2 gene is split into 21 exons, ranging in size from 53 to 516 bp, and spans an estimated 25 kb. The gene is transcribed in a 21cen-->21qter direction, with its 5' end mapping approximately 195 kb proximal to the 5' end of the phosphofructokinase-liver isoform gene. Four single base-pair polymorphisms were identified using single-stranded conformation polymorphism analysis. Possible functions of the protein based on homology to other members of the WD-repeat-containing family are discussed.